Risk for mortality in preoperative myocardial revascularization (Research, Society and Development, 2020)
To evaluate the risk of mortality in the preoperative period of myocardial revascularization through the application of EuroSCOREII by the nurse. Prospective, exploratory, quantitative study, developed in a private reference hospital in cardiac surgery, in Teresina-PI. The baseline population consisted of all preoperative patients with myocardial revascularization, aged 18 years, from August to 2018 January 2019. It included patients over 18 years of age, in the immediate preoperative period of myocardial revascularization undergoing surgery elective. Data was collected using the EuroSCOREII Scale, applied individually in the preoperative period. Mortality was verified after 30 days of surgery, to compare the established risk. The analysis of the study was through the EuroSCOREII, Excel and SPSS for the risk of mortality and the calculated risk and the mortality rate verified in the postoperative period of the patients were compared. The project was submitted to the ethics committee of the University Center Uninovafapi and received the approved opinion under 2,741,913. The socio-demographic profile of patients in the preoperative period of myocardial revascularization, 76 in total, showed that 82% were male. The mean age was 64.98 years and the highest number was between 60 and 69 years (41%). Mortality risk was divided into low (13%), medium (25%), medium high (31%), high (28%) and very high (3%). Patients with observed mortality were medium-high risk and belonging to the male gender. Mortality observed at 30 days was 2.63%. The prediction of mortality by EuroSCOREII was simple and applicable in myocardial revascularization in the studied Brazilian population and the mortality observed was close to the percentage of multicenter studies. This study contributes to the perception that this cardiac risk assessment score can be used by Nurses to identify risk of mortality and, through the calculated risk, to define nursing behaviors during cardiac surgeries and to improve the patient’s prognosis.